1992
DOI: 10.1088/0029-5515/32/6/i16
|View full text |Cite
|
Sign up to set email alerts
|

Velocity distribution of carbon atoms released from a tokamak limiter by chemical and physical sputtering

Abstract: The Doppler broadened profile of a C I line in the infrared (λ =909.5 nm, 3P2 to 3P20) has been measured with high spectral resolution (λ/Δλ > 105) in front of a graphite limiter in the TEXTOR tokamak. The line shows a strong Zeeman effect, but by selecting the pi component with a polarizer, the influence of the magnetic field of TEXTOR on the line shape can be practically eliminated, and the profile is determined only by the velocity distribution of the carbon atoms. By a comparison of shots with a 'detached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 10 publications
3
65
1
Order By: Relevance
“…This is especially true at the low plasma temperatures relevant to MARFE formation, where the release of carbon impurity is dominated by chemical sputtering. 17,18 Also, the dependence of hydrogen absorption and recycling properties on the wall coating material 19 can be of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true at the low plasma temperatures relevant to MARFE formation, where the release of carbon impurity is dominated by chemical sputtering. 17,18 Also, the dependence of hydrogen absorption and recycling properties on the wall coating material 19 can be of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…6 When physical sputtering seems dominant, effective temperatures can reach 5 eV, a value consistent with the energy spectrum of particles ejected directly by deuteron impact at energies of a few hundred eV. The first term on the right-hand side represents the influx of atomic carbon originating from heavy hydrocarbons and the second from the influx of methane.…”
Section: Introductionmentioning
confidence: 77%
“…It is important to establish if this is the case in order to provide confidence in the interpretation of the naturally emitted CI line wavelength profile, resulting from plasma impact on graphite surfaces, as a means of identifying the relative role of physical and chemical sputtering. In other studies [6][7][8], methane has been injected into tokamak plasmas through divertor targets or small openings in limiters. Although the latter studies also reported narrow CI profiles, indicative of rather cold C-atoms, the interpretation of such experiments is more difficult and subject to greater uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EL do not include four additional dissociative excitation channels for CH þ 4 that JR do, the ones leading to CH þ 2 , CH 2 , CH + , and C + . Since the Frank-Condon energy is distributed between the products of each breakup, in inverse proportion to the mass of the fragments, it had been conjectured [6] that the CI line should be about twice as broad for 12 CD 4 as for 12 CH 4 . As indicated by Table 1, however, there is little difference in the experimental CI profiles resulting from 12 CH 4 and 12 CD 4 puffing.…”
Section: Divimp Code Modelingmentioning
confidence: 99%